Avaliação da durabilidade de concretos fabricados com baixos teores de sílica de casca de arroz imersos em solução de sulfato de magnésio - Oldra, Gean (2015)
The sulfate ions are the main cause of concrete´s degradation. This is due to chemical reactions with concrete´s hydration products. Those chemical reactions result in compounds with greater volumes, generating internal tensions and decreasing concrete´s resistance hich can generate spalling and cracking. The main goal of this article is to study the effects of adding rice husk ash, which is obtained by burning it in fluid bed, in concrete, as well as, durability of concrete made with Portland cement type IV – Low heat of hydration (designated by ASTM) exposed to action of sulphate ions. To approach that goal, 75 x 15 x 15 cm concrete beams were casted and from each of those samples, 50 x 100 mm concrete specimens were removed by drilling the samples. After that drilling and extraction process, a part of the samples was dipped in a 7.5% magnesium sulfate solution and the other part was dipped in water. The weight of each sample was previously measured. A new weighing and compressive strength test were made on samples on 56th, 90th, 180th and 360th days. In concretes that were mixed, cement was replaced by silica in weight values of 0%, 3%, 5% and 10%. Results show that samples lost weight by spalling and leaching of soluble compounds. Moreover, there was also a decrease in compressive strength and the best results were obtained with the sample in which 10% of cement were replaced by 10% of silica.